Foreign direct investment and imperfect capital markets : count data analysis of Japanese FDI in the United States - Ho, Woon Yee (2008)
Between 1981 and 1990, FDI in Japan as a share of total US inward FDI increased four-fold. The increase coincided with the appreciating yen relative to the US dollar. While exchange rate changes can time FDI, Froot and Stein (1991) by assuming imperfect capital markets explain why exchange rate depreciation attracts FDI. Because imperfect capital markets due to asymmetric information makes external finance costly, it constrains firms from borrowing as much as they are willing to finance FDI. These borrowing constraints ease when the foreign currency depreciates resulting in increased relative wealth that can lead to increased FDI.